Detection of apoptosis by agarose gel electrophoresis in breast cancer patients - Kulig, Andrzej; Smolarz, Beata; Kozłowska, Elżbieta; Romanowicz-Makowska, Hanna; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
Purpose: Two alternative modes of cell death are distinguished: the first one is an accidental cell death (necrosis) and the second one is programmed cell death (apoptosis). The present study shows agarose gel electrophoresis method that should be used for a proper characterisation of cell death. Materials and methods. The apoptosis was analysed in blood cells of breast cancer patients (n = 60). Tissue samples were collected from 31 premenopausal women (mean age ±SD 42.34±4.52 years) and from 29 postmenopausal women (mean age ±SD 66.53±6.67 years). Blood samples from age matched healthy women served as control (n = 52). Results. The apoptotic cells were identified in 63% (38/60) of the breast cancers patients. The number of positive samples were significantly higher among cancer samples than among control samples (P <0.05). Conclusion. In the present work the high frequency of apoptotic peripheral blood cells in breast cancer using agarose gel electrophoresis methods was detected.